Variation in the timing of avian egg‐laying in relation to climate. Issue 3 (12th December 2018) - Englert Duursma, Daisy; Gallagher, Rachael V.; Griffith, Simon C.
Abstract : A significant proportion of birds around the world exhibit variation in the timing of egg‐laying, taking advantage of intermittent resource pulses to provision their offspring. Quantification of the climatic conditions associated with variation in breeding is essential for understanding reproductive phenology and adaptive responses to a changing climate. We use a novel dataset from Australia to test long‐established ideas about which climatic factors may govern avian breeding patterns. We combine ~146 000 breeding observations (first egg‐laying dates) from 327 species with daily measures of minimum temperature, maximum temperature and precipitation to examine the responsiveness of bird breeding to local climate conditions. Across five biomes we quantify and compare the difference in temperature and precipitation during each breeding event relative to 'average' conditions at each location (i.e. conditions during the one‐year period either side of a breeding event). For a smaller subset of species, we examine responses to temperature and precipitation in birds breeding across multiple biomes. These biomes are arrayed along Australia's north to south temperature gradient, and east to west aridity gradient. We found that breeding is non‐random in relation to climate. Within biomes, most species breed when temperature, precipitation, or both were distinctly different than the average conditions. Additionally, there is both intra‐ and inter‐specific variation in the climatic conditions under which species lay eggs across aridity and temperature gradients. Breeding in hot and arid regions is in part driven by the lagged effect of previous rainfall, however, hot temperatures are the primary constraint. These findings imply that opportunistic breeding in response to localised climate, independent of day‐length cues, may be relatively common in Australian birds. We conclude that breeding is likely closely associated with patterns of vegetation productivity and food resources, and limited by physiological stress resulting particularly from extreme temperature.